Contribution to cylindrical grinding of interrupted surfaces of hardened steel with medium grit wheel - Mello, Hamilton Jose de [UNESP]; Mello, Diego Rafael de [UNESP]; Rodriguez, Rafael Lemes [UNESP]; Lopes, Jose Claudio [UNESP]; Silva, Rosemar Batista da; Angelo Sanchez, Luiz Eduardo de [UNESP]; Hildebrandt, Rodolfo Alexandre [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2018)
Grinding is generally the first choice to provide combination of both superior surface finish and closer dimensional tolerances in a machined component. This process can be employed in manufacturing of continuous and interrupted surfaces. Crankshafts and engine piston rings are examples of ground precision mechanical components having interrupted surfaces. However, the specific literature about grinding of interrupted surfaces is still scarce. In this context, aiming to further contribute to the understanding of the behavior of surface integrity of interrupted surfaces during grinding, this paper presents an experimental investigation of interrupted surfaces ground with white aluminum oxide grinding wheel. Discs of AISI 4340 hardened steel with different number of grooves (2, 6, and 12) on the external surface were tested. Experiments with discs without interrupted surface were also carried out for comparisons. In addition to the number of grooves, three values of infeed rate (0.25, 0.50, and 0.75 mm/min) were used as input parameters. The output parameters investigated were the geometric errors (surface roughness and roundness) of the workpiece material as well as the diametric wheel wear. Analysis of variance (ANOVA) test was performed to verify any statistical difference among the output variables. Results showed that both surface finish and roundness of workpieces with interrupted surfaces were higher than those obtained for continuous surface. These parameters also increased with infeed rate up to 0.50 mm/min, whereas the grinding wheel wear was more sensitive to number of grooves and infeed rate. No thermal damages were observed on the machined workpieces under the conditions investigated.
Keywords: Cylindrical external plunge grinding; Interrupted surface; Number of grooves; AISI 4340 steel; Geometric errors; Wheel wear; Surface integrity